How BRCA and homologous recombination deficiency change therapeutic strategies in ovarian cancer: a review of literature - Arcieri, Martina; Tius, Veronica; Andreetta, Claudia; Restaino, Stefano; Biasioli, Anna; Poletto, Elena; Damante, Giuseppe; Ercoli, Alfredo; Driul, Lorenza; Fagotti, Anna; Lorusso, Domenica; Scambia, Giovanni; et al. (Frontiers in Oncology, 2024)
About 50% of High Grade Serous Ovarian Cancer exhibit a high degree of genomic instability due to mutation of genes involved in Homologous Recombination (HRD) and such defect accounts for synthetic lethality mechanism of PARP inhibitors (Parp-i). Several clinical trials have shown how BRCA and HRD mutational status profoundly affect first line chemotherapy as well as response to maintenance therapy with PARP-i, hence Progression Free Survival and Overall Survival. Consequently, there is urgent need for the development of increasingly reliable HRD tests, overcoming present limitations, as they play a key role in the diagnostic and therapeutic process as well as have a prognostic and predictive value. In this review we offer an overview of the state of the art regarding the actual knowledge about BRCA and HRD mutational status, the rationale of PARPi use and HRD testing (current and in development assays) and their implications in clinical practice and in the treatment decision process, in order to optimize and choose the best tailored therapy in patients with ovarian cancer.